2009
DOI: 10.1007/s10067-009-1180-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Andrographis paniculata composition for the relief of rheumatoid arthritis symptoms: a prospective randomized placebo-controlled trial

Abstract: Andrographis paniculata (Burm. f.) Wall ex Nees (Acanthaceae) possesses anti-inflammatory effects, attributed to the main constituent andrographolide proposed as alternative in the treatment of autoimmune disease. A prospective, randomized, double blind, and placebo-controlled study in patients with rheumatoid arthritis (RA) was performed. Tablets (Paractin) made of an extract of A. paniculata (30% total andrographolides) were administered three times a day for 14 weeks, after a 2-week washout period to 60 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 52 publications
2
79
0
Order By: Relevance
“…Consistent with prior studies, no differences in body weight and appearance were noticed between Andro-and solvent-treated mice. The safety of Andro is supported by a phase II clinical study of rheumatoid arthritis patients, which revealed that A. paniculata tablets containing 30 mg of andrographolide (three times a day for 14 weeks) were well tolerated and significantly more effective in reducing symptoms and serological parameters of the disease (Burgos et al, 2009). However, higher doses of Andro (4-6 mg/kg body weight, oral administration) may cause isolated cases of allergic reactions, tiredness, headache, pruritus/rash, diarrhea, nausea, metallic taste, bitter taste, and dry tongue (Coon and Ernst, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies, no differences in body weight and appearance were noticed between Andro-and solvent-treated mice. The safety of Andro is supported by a phase II clinical study of rheumatoid arthritis patients, which revealed that A. paniculata tablets containing 30 mg of andrographolide (three times a day for 14 weeks) were well tolerated and significantly more effective in reducing symptoms and serological parameters of the disease (Burgos et al, 2009). However, higher doses of Andro (4-6 mg/kg body weight, oral administration) may cause isolated cases of allergic reactions, tiredness, headache, pruritus/rash, diarrhea, nausea, metallic taste, bitter taste, and dry tongue (Coon and Ernst, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The effect was associated to a reduction of rheumatoid factor, IgA, and C4. The study concludes that the drug was significantly effective in reducing symptoms and serological parameters of the disease and therefore useful as natural complement in the treatment of Rheumatoid Arthritis [80].…”
Section: Efficacy Of An Andrographis Paniculata Composition (Paractinmentioning
confidence: 96%
“…In the literature, side effects associated with A. paniculata or andrographolide, administered in higher doses (4-6mg/kg), have caused isolated cases of allergic reactions, tiredness, headache, pruritus/rash, diarrhea, nausea, metallic taste, bitter taste, dry tongue, eyes sensitive to light, decreased short-term memory, dizziness, heartburn, tender lymph nodes, and lymphadenopathy [89]. None of these effects were observed in Rheumatoid Arthritis patients after 14 weeks of treatment [80].…”
Section: Efficacy Of An Andrographis Paniculata Composition (Paractinmentioning
confidence: 99%
See 2 more Smart Citations